2019
DOI: 10.2337/db18-1178
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Factor AGGF1-Primed Endothelial Progenitor Cells Repair Vascular Defect in Diabetic Mice

Abstract: Hyperglycemia-triggered vascular abnormalities are the most serious complications of diabetes mellitus (DM). The major cause of vascular dysfunction in DM is endothelial injury and dysfunction associated with the reduced number and dysfunction of endothelial progenitor cells (EPCs). A major challenge is to identify key regulators of EPCs to restore DM-associated vascular dysfunction. We show that EPCs from heterozygous knockout Aggf1+/− mice presented with impairment of proliferation, migration, angiogenesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 48 publications
0
33
0
1
Order By: Relevance
“…A novel signaling pathway, that is, angiogenic factor with G patch and FHA domains 1 (AGGF1)‐Akt‐Fyn‐Nrf2‐antioxidative genes, was also involved in the regulation of diabetic EPC function. AGGF1 activated Akt signaling, which inhibited Fyn‐mediated export and degradation of nuclear Nrf2; Nrf2 then binded to the promoter and regulatory region and activated the transcription of CAT, HO‐1, and NQO‐1, which reduced oxidative stress and improved the ischemia‐reparative capacity of transplanted EPCs in diabetic mice (Yao et al, 2019).…”
Section: Keap1‐nrf2 Signaling Pathway In Diabetic Vascular Injurymentioning
confidence: 99%
“…A novel signaling pathway, that is, angiogenic factor with G patch and FHA domains 1 (AGGF1)‐Akt‐Fyn‐Nrf2‐antioxidative genes, was also involved in the regulation of diabetic EPC function. AGGF1 activated Akt signaling, which inhibited Fyn‐mediated export and degradation of nuclear Nrf2; Nrf2 then binded to the promoter and regulatory region and activated the transcription of CAT, HO‐1, and NQO‐1, which reduced oxidative stress and improved the ischemia‐reparative capacity of transplanted EPCs in diabetic mice (Yao et al, 2019).…”
Section: Keap1‐nrf2 Signaling Pathway In Diabetic Vascular Injurymentioning
confidence: 99%
“…Besides angiogenesis, AGGF1 has been suggested to be involved in multiple other functions. It has been suggested that AGGF1 can fully reverse the effects of hyperglycaemia on endothelial progenitor cells [32]. AGGF1 may also inhibit TNF-a-mediated monocyte adhesion to endothelial cells and affect the expression of adhesion molecules and chemokines [17].…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation assays for HUVECs were carried out using the Cell Counting Kit‐8 (Dojindo, Kumamoto, Japan) as described 27‐29 . Cell migration was assessed using Transwell cell migration assays and wound scratch cell migration assays as described 27,30 . Endothelial cell tube formation assays were carried out with HUVECs cultured in 6‐well plates and transfected with METTL3 siRNA or treated with cycloleucine (40 mmol/L) for 36 hours as described 27,30,31 …”
Section: Methodsmentioning
confidence: 99%